Implementation of Automatic Car Cleaning System with Microcontroller System Atmega 8 - Catra Indra Cahyadi; Muhammad Fadlan Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The design is supported by several components such as the pump driving motor, control system, and sensors. The design is in the form of a miniature simulation or called a prototype on a small scale but with the same functionality and performance as the real size. A chip or integrated circuit (IC) technology is growing and becoming more sophisticated, thus providing opportunities for automation development through the Atmega 8 microcontroller. For example, car cleaning is done by human power. The idea arose to design and build a simpler but more useful automatic car wash system. The automatic car wash system uses a mechanical and electrical system that functions as a car wash tool that works automatically. By using several components such as ICs, capacitors, resistors, piezoelectric sensors, and Atmega 8 programmed with 12 volt and 5-volt power supplies. Based on the Atmega 8 microcontroller, the system works by pumping water and soap into the car and drying it with a blower. The input comes from the start user command, namely via the push-on button. Tests are carried out on all components connected to one system, when the start button is pressed the controller will start the car in the right position. The motor that drives the car starts and pulls the car inside. Then the water pump turns on automatically for 2 seconds to pour water into the car and is accompanied by spraying detergent for 2 seconds. After that, the car was rinsed with a cloth with a motor drive for 20 seconds. After that, the water is poured again into the car to clean the detergent residue for 5 seconds and then the last step is the drying process by a wind blower for 10 seconds until the car wash is finished.